Xq26.1‐26.2 gain identified on array comparative genomic hybridization in bilateral periventricular nodular heterotopia with overlying polymicrogyria. (23rd July 2014) - Abe, Yu; Kikuchi, Atsuo; Kobayashi, Satoru; Wakusawa, Keisuke; Tanaka, Soichiro; Inui, Takehiko; Kunishima, Shinji; Kure, Shigeo; Haginoya, Kazuhiro
Abstract : Periventricular nodular heterotopia (PNH) with overlying polymicrogyria (PMG) is a recently described, developmental brain malformation; however, the causative genes of this malformation have not yet been identified. We report on a 5‐year‐old Japanese male with bilateral PNH with overlying PMG. He had mild intellectual disability, distinctive facial features, short stature, and microcephaly, with cardiac disorders. No mutation was identified in Sanger sequences for FLNA and ARFGEF2 ; however, array comparative genomic hybridization revealed an approximately 0.8Mb gain at Xq26.1‐26.2, which included three genes: IGSF1, OR13H1, and FIRRE . We identified the same 3‐copy gain in his mother; despite identifying the same abnormality in the mother, it must still be considered as a possible cause for the abnormalities, as X‐inactivation in the mother could have led to her not expressing the same phenotype. This case may provide important clues for identifying the genes responsible and help in the understanding of the pathogenesis of this disorder. What this paper adds: PNH with PMG has been observed in association with a copy number gain of Xq26.1‐q26.2 containing the IGSF1, OR13H1, and FIRRE genes.